Educational Reform and Instructional Television In El Salvador - Wolff, Laurence; Agency for International Development (Department of State), Washington, DC. Bureau for Technical Assistance ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Instructional television played a significant role in El Salvador's efforts to reform grades 7, 8 and 9 of its educational system. The goals of the reform were to increase enrollments, eliminate tuition in public schools, lower failure rates, retrain teachers, improve the curriculum, and train students for service and technical careers. Changes in the system at least partially attributable to the use of instructional television (ITV) included a tripling of public school enrollments, increased student achievement, the development of positive attitudes toward education and technology, the improvement of teaching, and the general raising of educational aspirations. Other developing nations seeking educational reform can profit by following El Salvador's example regarding strong leadership and the use of a system approach, but should be cognizant of several attendant problems. These include: 1) the difficulty of providing personnel and facilities to produce ITV programing; 2) the need to uncover better ways of implementing change in traditional societies; 3) rising absolute costs, even when the system is cost-effective; and 4) the tendency of students to maintain unrealistic educational aspirations and to adhere to an outmoded but prestigious academic curriculum. (LB)
Educational level discussed: Grade 7.
Educational level discussed: Grade 8.
Educational level discussed: Grade 9.
Educational level discussed: Junior High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Aspiration; Developing Nations; Educational Change; Educational Development; Educational Innovation; Educational Technology; Educational Television; Grade 7.; Grade 8.; Grade 9.; Instructional Innovation; Junior High Schools; Program Descriptions; Program Evaluation; El Salvador; Educational Reform Program